2005
DOI: 10.4489/myco.2005.33.1.019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 'Azotobacter' Bioinoculant on the Growth and Substrate Utilization Potential ofPleurotus eousSeed Spawn

Abstract: We investigated the effect of nitrogen fixing Azotobacter bioinoculant on the mycelial growth and the rate of substrate utilization by Pleurotus eous. The synergistic or antagonistic role of the microorganism during dual culturing with the mushroom or the competitor molds Trichoderma viride, and Trichoderma reesi was studied. Azotobacter was inhibitory to the molds, which are competitive to the mushroom in the seed spawn substrate, but was synergistic towards the mushroom. The growth, substrate utilization pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Notably, some isolates in the study showed negative or no effect on the mushroom growth which could be due to the interaction between bacteria and fungi [6]. Our results are in agreement with previous studies, which have suggested the growth stimulatory role of bacteria [32]. Similar investigations of positive interaction were also reported during cocultivation of white-rot fungus P. florida and a fluorescent pseudomonas bacterium [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, some isolates in the study showed negative or no effect on the mushroom growth which could be due to the interaction between bacteria and fungi [6]. Our results are in agreement with previous studies, which have suggested the growth stimulatory role of bacteria [32]. Similar investigations of positive interaction were also reported during cocultivation of white-rot fungus P. florida and a fluorescent pseudomonas bacterium [16].…”
Section: Discussionsupporting
confidence: 92%
“…In a distinct study, Azotobacter sp. synergistically increased the linear growth of oyster mushroom P. eous [32]. Kim et al [17] reported that Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…After co-cultivation, the bacteria enhanced both radial and linear mycelial growth of P. orida. Eyini et al (2005) found that a low concentration (2mL/bottle) of fermentation broth of the nitrogen-xing bacterium Azotobacter can stimulate (18.28%) the mycelial growth of P. eous in spawn material, whereas a high concentration of the broth (10mL/bottle) inhibited the activity. Here, in submerged fermentation, all three isolates in uenced the mycelial growth rate, as evidenced by increased mycelial dry weight.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 lists the various substrate combinations designed for each Pleurotus spp. These amended substrates along with subsequent layers of mushroom grain spawn (10 % of dry weight) and 5 ml Azotobacter broth (pH = 7; cfu ~ 10 8 cells/ml), taken in place of gram powder as a source of nitrogen (Eyini et al 2005 ), were filled in the polythene bags (28 cm × 20 cm). Holes were made in these polythene bags for proper aeration.…”
Section: Methodsmentioning
confidence: 99%